Cevaplar

2012-11-05T18:31:39+02:00

P(x) e ax + b dersek P(x+1) = ax + a + b olur 

                              P(x - 2) = ax -2a + b olur 

 

 Bunlarıda 4x + 4 e eşitlememiz gerekiyor. eşitlersek ; P(x+1)+P(x-2) = 4x +4 

 

                                                                    ise ax + a + b + ax - 2a + b = 4x + 4

                                                                    ise 2ax - a + 2b = 4x + 4

                                                                    ozaman 2a =4  a =2 olur.

                                                                    2b - a = 4 olduğundan

                                                                    2b - 2 = 4                b = 3 olur

                      Böylece P(x) = 2x + 3 olur...  

0
2012-11-05T18:40:45+02:00

p(x)=ax+b

P(x+1)=ax+a+b

P(x-2)=ax-2a+b

P(x+1)+P(x-2)=2ax-a+2b=4x+4

a=2

b=3

P(x)=ax+b=2x+3

0